Effect of alloying elements on properties of aluminide-base intermetallic material developed via powder metallurgy route. - Hussain, Zuhailawati; Bakir Hussain, Luay; Ismail, Ahmad Badri (Universiti Sains Malaysia, 2007)

(untitled)
The present study deals with the effect of additive element on structure and properties of Fe-Al intermetallic. FeAl-based intermetallic alloys with chromium or molybdenum addition were fabricated by s intering of mechanically alloyed powders.